Front Cover: Arrestin‐Domain Containing Protein 1 (Arrdc1) Regulates the Protein Cargo and Release of Extracellular Vesicles. Issue 17 (3rd September 2018) - Anand, Sushma; Foot, Natalie; Ang, Ching‐Seng; Gembus, Kelly M.; Keerthikumar, Shivakumar; Adda, Christopher G.; Mathivanan, Suresh; Kumar, Sharad
Abstract : DOI:10.1002/pmic.201800266 In article number1800266, Anand et al. report that the Arrestin‐domain‐containing protein 1 (Arrdc1) regulates the secretion and the protein cargo of extracellular vesicles. Depletion of Arrdc1 results in a significant reduction of the secretion of extracellular vesicles and alters the protein cargo packaged within these membranous vesicles. The cover image shows the secretion of exosomes and ectosomes by mammalian cells.